Development and evaluation of a solar powered automated fertigation system - ANJALY C. SUNNY; Dr. Abdul Hakkim V. M (Guide) (tavanur 2016 DEPARTMENT OF LAND AND WATER RESOURCES CONSERVATION ENGINEERING)
Development and evaluation of a solar powered automated fertigation system
Development and evaluation of a solar powered automated fertigation system